CD19 CAR T cells are an effective therapy for posttransplant relapse in patients with B-lineage ALL: real-world data from Germany - Bader, Peter; Rossig, Claudia; Hutter, Martin; Ayuk, Francis Ayuketang; Baldus, Claudia D.; Bücklein, Veit L.; Bonig, Halvard; Cario, Gunnar; Einsele, Hermann; Holtick, Udo; Koenecke, Christian; Bakhtiar, Shahrzad; et al. (Blood Advances, 2023)
Patients with precursor B-cell acute lymphoblastic leukemia (pB-ALL) who have relapsed after allogeneic hematopoietic stem cell transplantation (allo-HSCT), have relapsed more than once, or are resistant upfront have a dismal prognosis. CD19-targeted chimeric antigen receptor (CAR) T cells have evolved as potent immune therapies. Tisagenlecleucel (Tisa-cel) is a commercially available autologous CD19-directed CAR T-cell product. We performed a retrospective study inviting all CAR T-cell centers in Germany to participate. Eighty-one patients with pB-ALL were included. Twenty-eight days after CAR T-cell infusion, 71 patients (87.7%) were in complete response, and 8 (9.9%) were in nonremission. At 2 years, the probabilities of event-free survival (pEFS), relapse-free survival (pRFS), and overall survival (pOS) were 45.3%, 51.7%, and 53.2%, respectively. pEFS was not different in patients without (n = 16, 55.0%) vs with prior allo-HSCT (n = 65, 43.4%). In patients treated after allo-HSCT, the time to relapse after allo-HSCT was a strong predictor of outcome. Patients relapsing within 6 months of allo-HSCT had a disappointing pEFS of 18.4% (pOS = 16.0%); the pEFS for those relapsing later was 55.5% (pOS = 74.8%). Our study provides real-world experience in pediatric, adolescent, and young adult patients with ALL treated with Tisa-cel, where most patients were treated after having relapsed after allo-HSCT. A total of 45.3% were rescued with a single dose of Tisa-cel. Our novel finding that patients with ALL after allo-HSCT had by far a better pEFS if relapse occurred beyond 6 months might be helpful in clinical decision-making and motivates studies to uncover the reasons.
CRIS-Team Scopus Importer:2023-08-25